2001
DOI: 10.1007/s002770100297
|View full text |Cite
|
Sign up to set email alerts
|

CD20-positive T cell leukemia/lymphoma: case report and review of the literature

Abstract: We report on a case of CD20-positive peripheral T cell lymphoma. The lymphoma cell was positive for CD20 and T cell lineage markers such as cytoplasmic CD3, CD4, and CD5 and had a monoclonal rearrangement of the T cell receptor (TCR) gamma chain gene. The clinical characteristics resembled angioimmunoblastic lymphadenopathy: spontaneous regression of lymphadenopathy and immunological abnormalities such as polyclonal hypergammaglobulinemia, positive results of direct and indirect antiglobulin tests, and a high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…Co-expression of both T- and B-cell markers was in agreement with expression patterns of neoplastic T-cells showing positive signals for CD3, CD4, CD5, CD8, CD45, and CD20 and negative signals for other B-cell markers such as CD79a and PAX522. Some specific type of B-cell lymphomas show negative staining for CD2023 while some T-cell lymphomas show positive staining for CD2024. It is suggested that although CD markers are specific to particular cell types but in neoplastic conditions their expression becomes non-specific7.…”
Section: Discussionsupporting
confidence: 77%
“…Co-expression of both T- and B-cell markers was in agreement with expression patterns of neoplastic T-cells showing positive signals for CD3, CD4, CD5, CD8, CD45, and CD20 and negative signals for other B-cell markers such as CD79a and PAX522. Some specific type of B-cell lymphomas show negative staining for CD2023 while some T-cell lymphomas show positive staining for CD2024. It is suggested that although CD markers are specific to particular cell types but in neoplastic conditions their expression becomes non-specific7.…”
Section: Discussionsupporting
confidence: 77%
“…Whilst expression of CD20 has been reported in T-cell lymphomas [6], this case is one of only very few published observations of CD20 expression in AITL and is unique in that the CD20 expression was acquired upon relapse. The first case of CD20-positive AITL was reported by Yokose et al as peripheral T-cell lymphoma with clinical characteristics resembling angioimmunoblastic lymphadenopathy [7]. The second report was by Tachibana et al in 2011 [8] with features very similar to the herein presented case, in particular also the acquisition of CD20 expression upon disease progression.…”
Section: Discussionsupporting
confidence: 60%
“…Although rare CD20 + B cells that express CD3 have been reported to exist (Yokose et al, 2001; Wang et al, 2009; Perez-Andres et al, 2011), normal B1 cells do not express CD3 (Griffin et al, 2011b). The addition of CD3-negative gating also reduces concerns that positive staining for any marker results from high autofluorescence and/or non-specific binding and is thus artifactual.…”
Section: Resultsmentioning
confidence: 99%